Long COVID-19 Syndrome and Frailty: Cause or Consequence or Both? - Ray, Marks (Journal of Aging Research And Healthcare, 2023)
Background Many older adults remain vulnerable to COVID-19 infections. They are also often at risk for frailty and poor health outcomes.  Aim This exploratory review examines the correlates of long COVID and frailty and their association insofar as the older adult’s wellbeing may be jeopardized.  Methods and procedures Articles that emerged between January 1 2022 and 2023 in major electronic data bases that addressed the current topic of interest were sought using the key words: Long COVID and Frailty. Those deemed relevant were duly downloaded, analyzed and summarized in narrative form.  Results A high proportion of older adults can be expected to remain vulnerable to COVID-19 long term impacts, plus new variants of infection, along with frailty as both an outcome and mediator. Many too are at risk for persistent long COVID-19 complications and a low life quality if more concerted preventive and rehabilitation efforts to avert frailty early on are not forthcoming in a timely manner.  Conclusion Prompt and continuing frailty assessments of older adults at risk for COVID-19 or recovering from this disease, especially those with long COVID manifestations who are frail or may become frail are strongly indicated.
Keywords: COVID-19; Frailty; Long COVID; Intervention; Post-acute COVID; Prevention